-7x-8y=-3

Add 7x to both sides of the equation.

-8y=-3+7x

Divide each term in -8y=-3+7x by -8.

-8y-8=-3-8+7x-8

Cancel the common factor of -8.

Cancel the common factor.

-8y-8=-3-8+7x-8

Divide y by 1.

y=-3-8+7x-8

y=-3-8+7x-8

Simplify each term.

Dividing two negative values results in a positive value.

y=38+7x-8

Move the negative in front of the fraction.

y=38-7×8

y=38-7×8

y=38-7×8

The given equation y=38-7×8 can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation -7x-8y=-3